HUBUNGAN KECEMASAN DENGAN KADAR GLUKOSA DARAH PENDERITA DIABETES MELLITUS DI WILAYAH KERJA PUSKESMAS SUMBERSARI BANTUL KEC. METRO SELATAN KOTA METRO - Ludiana Ludiana (JURNAL WACANA KESEHATAN, 2017)
Diabetes mellitus is a chronic metabolic disorder marked increase in blood glucose. According to the World Health Organization (WHO) in 2013 the incidence of diabetes mellitus in the world reached 347 million people in Indonesia alone ranks among the seven countries with the highest diabetes prevalence of 7.6 million people. Among the causes of the increase in blood glucose levels in diabetics is due to psychological factors, namely anxiety. In the pre-survey results in Puskesmas Sumbersari Bantul note that from 8 patients with diabetes mellitus, there are 6 people experiencing anxiety and 2 do not complain any signs of anxiety. The purpose of this study was to determine the relationship of anxiety with blood glucose levels of diabetics mellitus in Puskesmas Sumbersari Bantul District of South Metro City. The type quantitative research, form design used is cross sectional. The population in this study are patients with diabetes mellitus in Puskesmas Sumbersari Bantul District of South Metro totaling 408 samples taken as many as 41 people. The analysis in this study using the test Person Product Moment. Statistical analysis showed that anxiety patients with diabetes mellitus are at an average score of 27.44 with a standard deviation of 4.353 and the average blood sugar levels of people with diabetes mellitus are at 339.78 mg / dL with a standard deviation of 74.742. In the Person Product Moment test results proved no relationship anxiety with blood sugar levels of people with diabetes mellitus (p-value = 0.000 <a 0.05). Pearson correlation results obtained value of 0.817 towards a positive correlation with the strength of the relationship is very strong. Conclusions research shows there is an anxiety relationship with blood glucose levels of diabetics mellitus.